2011
DOI: 10.1007/s10495-011-0591-3
|View full text |Cite
|
Sign up to set email alerts
|

PI3 Kinase inhibition on TRAIL-induced apoptosis correlates with androgen-sensitivity and p21 expression in prostate cancer cells

Abstract: TNF-related apoptosis-inducing ligand (TRAIL) can induce apoptosis in many types of cancer cells. TRAIL is considered a therapeutic target, therefore, it was of interest to examine molecular mechanisms that may modulate sensitivity to TRAIL signaling in prostate cancer cells. LNCaP cells were found to be relatively resistant to TRAIL induced cell death while PC3 cells were sensitive. PI3-kinase (PI3 K) inhibitors were able to render LNCaP cells sensitive to TRAIL but conferred resistance to PC3 cells. PI3 K in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In case of DU145 cells, the increased expression of p21 is consistent with blockage of cell cycle since the number of proliferating viable cells is diminished after administration of imatinib. On the other hand, there are reports stating that p21 confers resistance to imatinib induced‐apoptosis in human chronic myeloid leukemia cells , and that it induces resistance to treatment in cases of PCa . Therefore, it is liable to assume that a similar mechanism is occurring in PC3 cells, which would explain the increased cell viability following treatment with imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…In case of DU145 cells, the increased expression of p21 is consistent with blockage of cell cycle since the number of proliferating viable cells is diminished after administration of imatinib. On the other hand, there are reports stating that p21 confers resistance to imatinib induced‐apoptosis in human chronic myeloid leukemia cells , and that it induces resistance to treatment in cases of PCa . Therefore, it is liable to assume that a similar mechanism is occurring in PC3 cells, which would explain the increased cell viability following treatment with imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Kadowaki et al found that the AR-positive LNCaP cells were resistant to TRAIL-induced apoptosis, while the AR-negative PC-3 cells were sensitive 87 , suggesting AR might play negative roles in this type of apoptosis. Rokhlin et al also revealed that increased AKT might suppress the androgen-inhibited apoptosis 52 .…”
Section: Differential Ar Roles In 5 Types Of Pca Cell Deathmentioning
confidence: 99%
“…It is able to target a wide range of tumor cells without affecting normal cells [ 11 ]. TRAIL-mediated cancer cell killing can occur via both extrinsic and intrinsic apoptotic pathways [ 12 ]. TRAIL triggers apoptotic signals through bindings to its death receptors, (DR4 and DR5) [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…TRAIL-mediated cancer cell killing can occur via both extrinsic and intrinsic apoptotic pathways [ 12 ]. TRAIL triggers apoptotic signals through bindings to its death receptors, (DR4 and DR5) [ 12 , 13 ]. The interaction between TRAIL and its receptors triggers the recruitment of the Fas-associated death domain (FADD), facilitating the subsequent recruitment of procaspase-8 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%